2019
DOI: 10.1111/xen.12552
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐bone bone marrow transplantation from hCD47 transgenic pigs to baboons prolongs chimerism to >60 days and promotes increased porcine lung transplant survival

Abstract: Background We have recently demonstrated that human‐CD47 (hCD47) expressed on endothelial cells of porcine lung xenografts extended median graft survival from 3.5 days to 8.7 days in baboons. Intra‐bone bone marrow transplantation (IBBMTx) in a pig‐to‐baboon model was previously shown to markedly prolong the duration of macrochimerism up to 21 days from 1 to 4 days by intravenous BMTx. We now examined whether the use of hCD47 transgenic (Tg) BM further prolonged the duration of chimerism following IBBMTx. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 34 publications
1
36
0
1
Order By: Relevance
“…The longest survival time for orthotopic liver xenografts (29 days) was achieved using GGTA1 knock-out pigs, exogenous human coagulation factors, and immunosuppression, including co-stimulation blockade [104]. In turn, Watanabe et al demonstrated prolonged survival time of lung xenotransplants (14 days) from GGTA1 knock-out, hCD47/hCD55 donor pigs in immunosuppressed baboons [105]. The authors indicated the important role of hCD47 expression in reducing immunologic damages and extending lung graft survival in the pig-to-NHP model.…”
Section: Preclinical Studies In Xenotransplantationmentioning
confidence: 99%
“…The longest survival time for orthotopic liver xenografts (29 days) was achieved using GGTA1 knock-out pigs, exogenous human coagulation factors, and immunosuppression, including co-stimulation blockade [104]. In turn, Watanabe et al demonstrated prolonged survival time of lung xenotransplants (14 days) from GGTA1 knock-out, hCD47/hCD55 donor pigs in immunosuppressed baboons [105]. The authors indicated the important role of hCD47 expression in reducing immunologic damages and extending lung graft survival in the pig-to-NHP model.…”
Section: Preclinical Studies In Xenotransplantationmentioning
confidence: 99%
“…However, the xenografts were functional for only 3.5 h because of severe coagulation dysregulation (179). Recently, Watanabe et al reported that the survival time of NHP recipients of lungs from GTKO/CD47/CD55 transgenic pigs was extended by 14 days (163,180). These studies have demonstrated that the introduction of hCD47 can mitigate acute vascular rejection of lung xenografts and prolong porcine lung transplant survival time in NHP models.…”
Section: Lung Xenotransplantationmentioning
confidence: 99%
“…Xenogeneic chimerism supported tolerance of recipient T and B cells towards lung xenograft. The porcine lung grafts used in this study carried three genetic modifications (GTKO/CD47/CD55) (Watanabe et al., 2019). Another study reported a prolonged lung xenograft survival of 31 days on a life‐supporting model.…”
Section: Pancreatic Isletsmentioning
confidence: 99%